A Study on the politeness strategies used by U.P. Varsity Team Captains in face-threatening situations encountered with their coaches - Alarcon, Angela Shayna C.; Jamandre, Neil Kenneth F. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
The "face" is the desired self-image that individuals present in their everyday lives. It is also a social activity composed of verbal and non-verbal communication, which is primarily displayed through the way individuals communicate and interact (Redmond, 2015.) When the face is lost or damaged, Face-Threatening Acts (FTAs) take place. These kinds of FTAs may intentionally or unintentionally threaten the face, with the use of verbal and non-verbal speech acts which challenge the wants of the hearer or the speaker. This qualitative study sought to answer the question: "How do selected UP Diliman varsity team captains respond to face-threatening situations encountered with their coaches?" With the following objectives: 1) to describe the face-threatening situations that the team captains encounter in the interactions with their coaches during training; 2) to describe the politeness strategies used by team captains during face-threatening situations in training; 3) to describe how the politeness strategies are used by the team captains in adapting to face-threatening situations during training. The theoretical framework of the study consisted of the Politeness Theory by Brown and Levinson (1978) and Symbolic Interaction Theory by Herbert Blumer (1969). In-depth interviews of 17 team captains from the men and women's individual sports team from the University of the Philippines-Diliman were conducted to ensure that the research objectives of the study were met. From the data gathered, the face-threatening situations identified were categorized into verbal, paraverbal and non-verbal. The veral face-threatening situations were the language used by the coaches such as their offensive remarks, foul language, insensitive comments about the team captain's physical appearance and private lives. The paraverbal face-threatening situations wre the coaches' tone and quality of voice (shouting, raising of the voice, sarcasm in tone). The non-verbl face-threatening situations were the coaches' facial expressions, gestures (pointing fingers), body movements (walking out, throwing objects, showing tantrums) and silence. Participants chose the Avoidance strategy because respect to their coach and hierarchy as to who is more in authority is given the utmost importance. Positive politeness was the next chosen strategy as they choose to lighten the situation by smiling, joking, laughing and expressing familiarity between the relationship as humour eases the tension and awkwardness present in the interaction. Team captains used the negative politeness strategy to be accepted and validated by the coach with the excessive use of apologies and compensation, as such face-threatening incidents lead to subservient actions just to regain themselves. As for the Bald on Record strategy, it is driven by the team captain's need to vent out their emotions and frustrations to their peers, as they would not be direct about certain matters because they do not want to ruin the coach's image or they are trying to be careful about the situation to avoid judgment.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.